Poetic interventions in the imagined city: an approach to Juan Gallego Benot's «La ciudad sin imágenes» (Castilla. Estudios de Literatura, 2024)
The main character of La ciudad sin imágenes (2023) suffers from prosopagnosia, a cognitive illness that prevents him from retaining images in his memory. The available image he retains of the city consequently ceases to operate as a guiding element of his motor and orientative capacity for the urban environment and cedes to the poetic word, with its particular characteristics, the relay for the meaning and significance of the urban environment. In this article, we analyse the characteristics and theoretical possibilities of a poetry that is not subsidiary to the external image and, once its particularities have been delimited, we address the possibilities that such an understanding of the poetic logos presents for the city of the 21st century; that is, to what extent it frees it from outdated symbologies and invites the reader to reconsider its frameworks.
Keywords: contemporary poetry; language poetry; visual culture; space studies